PROFITABILITAS, LEVERAGE, KOMPOSISI DEWAN KOMISARIS, KOMITE AUDIT, DAN KOMPENSASI RUGI FISKAL TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN PERBANKAN - DEWI PUTRININGSIH; EKO SUYONO; ELIADA HERWIYANTI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2018)
Tax avoidance has been a main concern of almost in the world. It is mostly done by tax payer due to its legality. This study aims to analyze factors affecting tax avoidance (i.e, profitability, leverage, independent bord, audit committee, and fiscal loss compensation) with firm size as a control variable. Implementing purposive sampling approach, this study ended-up with 30 companies for 2011-2015 period (i.e., 150 observations). By using OLS regression, the findings shows that profitability influences positively on tax avoidance, meanwhile, leverage and fiscal loss compensation affect negatively on tax avoidance. Moreover, corporate governace mechanisms (i.e., independent board and audit committee) and firm size as a control variable do not have a significant influence on tax avoidance. Therefore, this study contribute to providing empirical evidence on factors affecting tax avoidance in Indonesian banking companies.